2012
DOI: 10.1182/blood-2011-12-400580
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of SOX11 in a population-based cohort of mantle cell lymphoma

Abstract: The prognostic role of the transcription factor SOX11 in mantle cell lymphoma (MCL) is controversial. We investigated prognostic markers in a population-based cohort of 186 MCL cases. Seventeen patients (9%) did not require any therapy within the first 2 years after diagnosis and were retrospectively defined as having an indolent disease. As expected, indolent MCL had less frequent B symptoms and extensive nodal involvement and 88% of these cases expressed SOX11.In our cohort 13 cases (7.5%) lacked nuclear SOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
104
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 40 publications
8
104
3
Order By: Relevance
“…7 The relationship between the absence of SOX11 expression and an indolent clinical behavior of these tumors has been confirmed in subsequent studies [8][9][10] but not in others. 11 However, most aggressive SOX11-negative mantle cell lymphoma carry also TP53 mutations and may, therefore, correspond to a transformed form of these tumors. 10,11 The oncogenic potential of SOX11 has been confirmed experimentally by SOX11-knockdown studies that have shown a significant reduction of tumor growth in vivo of xenografted SOX11-negative mantle cell lymphoma cell lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 The relationship between the absence of SOX11 expression and an indolent clinical behavior of these tumors has been confirmed in subsequent studies [8][9][10] but not in others. 11 However, most aggressive SOX11-negative mantle cell lymphoma carry also TP53 mutations and may, therefore, correspond to a transformed form of these tumors. 10,11 The oncogenic potential of SOX11 has been confirmed experimentally by SOX11-knockdown studies that have shown a significant reduction of tumor growth in vivo of xenografted SOX11-negative mantle cell lymphoma cell lines.…”
mentioning
confidence: 99%
“…11 However, most aggressive SOX11-negative mantle cell lymphoma carry also TP53 mutations and may, therefore, correspond to a transformed form of these tumors. 10,11 The oncogenic potential of SOX11 has been confirmed experimentally by SOX11-knockdown studies that have shown a significant reduction of tumor growth in vivo of xenografted SOX11-negative mantle cell lymphoma cell lines. 12,13 The oncogenic mechanisms of SOX11 in mantle cell lymphoma pathogenesis are not well understood.…”
mentioning
confidence: 99%
“…The indolent subgroup accounts for 10-15% of all MCL cases. Despite the fact that this MCL subgroup shows no signs of progression for a long period of time, the majority of patients face a relatively rapid disease progression, short-term response to treatment, inevitable relapses and a continuously declining survival curve, with a median survival of only 3-5 years (17)(18)(19). The following clinical factors have been associated with poor prognosis of MCL: Advanced age, poor general condition, advanced stage of the disease, splenomegaly, elevated LDH, low serum albumin, other tumors and anemia.…”
Section: A B Cmentioning
confidence: 99%
“…SOX11 has been associated with improved overall survival in two studies including 53 and 186 patients respectively. 45,57 In contrast, SOX11 expression has also been identified as a discriminating antigen between indolent MCL (SOX11 negative) and aggressive MCL (SOX11 positive), thus correlating SOX11 expression to poorer outcome and lack of hypermutation of V H genes. 46,47 This is in contrary to studies presented by Nygren et al and Kuo et al, which concluded that most of their indolent MCL patients were SOX11 positive.…”
Section: Sox11 As a Prognostic Toolmentioning
confidence: 99%
“…46,47 This is in contrary to studies presented by Nygren et al and Kuo et al, which concluded that most of their indolent MCL patients were SOX11 positive. 49,57 Recently, two independent studies associated increased SOX11 expression with improved overall survival in patients treated with either the Nordic protocol 22 ( Figure 1A) or with R-Hyper-CVAD 49 pin-pointing a role of SOX11 as a predictive biomarker for these treatments.…”
Section: Sox11 As a Prognostic Toolmentioning
confidence: 99%